Les peuplements d'Okoumes eclaircis au Gabon - Fuhr, M.; Nasi, Robert; Minkoue, J.M. (1998)
The continuous monitoring from 1988 to 1995 of thinned and control Okoumé stands in the coastal forest of Gabon helps to evaluate the relevance of silvicultural treatment with regard to sustainable management. The stands, almost even-aged, are grouped according to their ages. The homogeneity of structural features between future thinned and control stands is verified. The thinning, carried out in 1989, is a selective thinning in the upper storey. The average removal of basal area is 36 % in young stands (15 to 30 years old) and 21 % in older ones (37 to 50 years old). More than 80 % comes from supernumerary dominant Okoumé trees (average volume at 7 cm diameter removed in older stands : 145 M3/haj. Six years after thinning, young and old stands have reacted favourably. The dominant population is not significantly weakened. The gain on average current diameter annual increment of Okoumé trees stabilized around 0,2 to 0,3 cm/yr. Related to the increment before thinning, this gain is substantial for dominated and small dominant trees but minor for big dominant trees. At stand level, the better growth of remaining trees not offset the loss of basal area due to thinning. In stands where the Okoumé accounts for more than 80 % of total basal area, the removal of large usable trees is too sizeable for thinning after 35 years to be relevant. This may not be the case in more mixed forests where the Okoumé represents only 30-80 % of total basal area, and the relevance of thinning in such stands